Cavitation and Induced Excitation Force of Ice-Class Propeller Blocked by Ice - Pei Xu; Chao Wang; Liyu Ye; Chunyu Guo; Weipeng Xiong; Shen Wu (Journal of Marine Science and Engineering, 2021)
The presence of broken ice in the flow field around a propeller causes severe blade erosion, shafting, and hull vibration. This study investigates the performance of the propeller of a ship sailing in the polar regions under the propeller–ice non-contact condition. To this end, we construct a test platform for the propeller-induced excitation force due to ice blockage in a large circulating water channel. The hydrodynamic load of the propeller, and the cavitation and propeller-induced fluctuating pressure, were measured and observed by varying the cavitation number and ice–propeller axial distance under atmospheric pressure and decompression conditions. The results show that the fluctuation range of the blade load increases with a decrease in cavitation number and ice–propeller axial distance. The decrease in the cavitation number leads to broadband characteristics in the frequency-domain curves of the propeller thrust coefficient and blade-bearing force. Under the combined effects of ice blockage and proximity, propeller suction, the circumfluence zone around the ice, and the Pirouette effect, propeller–hull vortex cavitation is generated between the ice and propeller. The decrease in cavitation number leads to a sharp increase in the amplitude of the high-order frequency of the propeller-induced fluctuating pressure.